The Importance of Learning a Foreign Language: A Gateway to Understanding Lifestyle, Customs, and Values - Azimova Husnora Sunatillo qizi; Musurmanova Shakhnoza Kuchkarovna (Scientific Trends, 2024)
In this article is given about how language learning fosters cross-cultural awareness, enhances personal growth, and promotes empathy in an ever-diversifying global society. In an increasingly interconnected world, the ability to communicate across cultural boundaries has never been more vital. Learning a foreign language serves as a powerful tool that goes beyond mere vocabulary and grammar; it opens doors to understanding the lifestyle, customs, and values of other peoples.
Keywords: Cultural boundaries, global society, interconnected world, harmony, social hierarchies, language development, interpersonal dynamics, cohesion.